Evaluasi Penetapan Tarif Air Minum Pada Blud Air Minum Kota Cimahi - Yuyun Kurniawati; Khariidatul Bahiyyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Clean water is one of the necessities of life. Almost all human activities require clean water, from drinking, bathing, cooking, washing and other activities. In Indonesia, Regional Drinking Water Companies (PDAMs) are responsible for community drinking water services. The Cimahi City Government organized drinking water services for the community by providing UPTD Air Minum in 2014 and became BLUD Air Minum in 2020 to gain more flexibility in managing the economy. BLUD Cimahi City's revenue comes from water sales, so it is expected that the fixed tariff will get optimal revenue while being able to cover company expenses. One of the principles of water tariff setting is full cost coverage, i.e. that all company costs can be covered by tariff revenues. Therefore, to achieve this principle, a Break Even Point calculation is conducted, i.e. where the total revenue from the sales volume is equal to the total costs. Through this research, it can be determined whether the drinking water tariff of BLUD Air Minum Cimahi City can cover all company costs. The research used is a qualitative and descriptive approach. Information was obtained through interviews and documentation. The results of this study indicate that BLUD Air Minum is appropriate in setting the Drinking Water tariff, because at the beginning of the fourth quarter or October, the Drinking Water tariff revenue has reached the break-even point.Keywords: Tariff, Cost, Break Even Point Keywords: Tariff, Cost, Break Even Point